Hallandose este gobierno sin secretario para su despacho á causa de hallarse prisionero por la autoridad militar el individuo que obtenía este empleo . ([publisher not identified], 1835)
Circular announcing that, since the secretary has been taken prisoner by the military authorities, Santiago del Valle has been appointed and sworn in as secretary ad interim.